(untitled) (Research, Society and Development, 2022)
In Introduction: Although there are laws and programs for the inclusion of disabled persons in higher education, there are still barriers, especially regarding the path during the course and the teaching methodologies. Objective: Verify the scenario of higher education in the health area for disabled persons. Materials and methods: An integrative review was carried out, through a high sensitivity search in the databases: PubMed and Scopus, and in the portal: Virtual Health Library, using the descriptors "disabled persons", "autism spectrum disorder", "education graduate" and "catchment area, health" related to the Boolean operators AND and OR. The screening of the articles found was carried out using the Rayyan® application. Results: A total of 1896 studies were found in the search. After reading the title, abstract and full article, 30 studies were included. These were published between 2006 and 2021, most of them in Portuguese, and the others in English and Spanish. Among these, only six were specifically about teaching in the health area. Furthermore, the articles highlighted the different challenges of teaching disabled persons, which permeate the social, pedagogical, and structural spheres. Conclusion: There are advances in the inclusion of disabled persons in health courses in higher education, but there are still many challenges and few published studies. The challenges are related to the competence of professionals for teaching this group and the role of educational institutions as support providers.